2017
DOI: 10.1016/j.freeradbiomed.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

D-penicillamine combined with inhibitors of hydroperoxide metabolism enhances lung and breast cancer cell responses to radiation and carboplatin via H 2 O 2 -mediated oxidative stress

Abstract: D-penicillamine (DPEN), a copper chelator, has been used in the treatment of Wilson's disease, cystinuria, and rheumatoid arthritis. Recent evidence suggests that DPEN in combination with biologically relevant copper (Cu) concentrations generates H2O2 in cancer cell cultures, but the effects of this on cancer cell responses to ionizing radiation and chemotherapy are unknown. Increased steady-state levels of H2O2 were detected in MB231 breast and H1299 lung cancer cells following treatment with DPEN (100 μM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…The active sites of TrxR, -Cys-Val-Asn-Val-Gly-Cys-on the Nterminal side and -Gly-Cys-SeCys-Gly on the C-terminus, are essential for its enzyme activity. Because auranofin has high affinity for protein thiol and selenol groups, 20,68) it is thought that it binds the active sites of TrxR and inhibits its activity. Auranofin-induced inhibition of TrxR causes the accumulation of ROS in cells and induces apoptosis and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The active sites of TrxR, -Cys-Val-Asn-Val-Gly-Cys-on the Nterminal side and -Gly-Cys-SeCys-Gly on the C-terminus, are essential for its enzyme activity. Because auranofin has high affinity for protein thiol and selenol groups, 20,68) it is thought that it binds the active sites of TrxR and inhibits its activity. Auranofin-induced inhibition of TrxR causes the accumulation of ROS in cells and induces apoptosis and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes provide the first line of defense against the deleterious effects of ROS [45]. SOD catalyzes the dismutation of superoxide radicals to hydrogen peroxide (H 2 O 2 ) and molecular oxygen, whereas catalase (CAT) and glutathioneperoxidase (GSH-PX) are responsible for H 2 O 2 detoxification [46]. The decreased activity of SOD leads to the increased production of MDA via the catalytic cracking of lipid peroxides in the presence of metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cancer tissue has elevated copper levels when compared with normal tissue (37, 38). This elevated copper can interact with copper chelators such as D -penicillamine and disulfiram, causing induction of oxidative stress (3941). D-penicillamine is a repurposed drug that was previously used for treatment of Wilson’s disease and rheumatoid arthritis (41).…”
Section: Example 2: Drug Repurposing For Tumor Sensitizationmentioning
confidence: 99%
“…Disulfiram is used for the treatment of alcoholism (42). Both of these agents are now being investigated as anti-cancer drugs and have shown promise when combined with both chemotherapy and radiation (39, 43, 44). Notably, studies have shown that disulfiram is safe and tolerable in patients treated for both glioblastoma and NSCLC in combination with standard chemotherapies (43, 44).…”
Section: Example 2: Drug Repurposing For Tumor Sensitizationmentioning
confidence: 99%